High expression of DGKA indicates poor overall survival of nasopharyngeal carcinoma - Hao Chen; Runduan Lin; Qi Yuan; Xiaohang Gao; Lin Zhang; Rong Zhang (Discover Oncology)
Abstract Background Nasopharyngeal carcinoma (NPC) is a malignant tumor with strong tendency of metastasis and recurrence. Therefore, prognostic indicators for NPC are urgently needed. DGKA is overexpressed in many cancers. However, the role of DGKA in NPC remains unclear. The aim of this study is to investigate the expression patterns and prognostic value of DGKA in NPC. Methods The mRNA expression of DGKA was analyzed from the dataset of The Cancer Genome Atlas (TCGA). Immunohistochemistry was performed to detect the expression of DGKA in 124 paraffin-embedded samples. Survival analysis was conducted according to the Kaplan–Meier method. Univariate and multivariate Cox regression analyses were used to identify the independent prognostic factors. Results We found the mRNA expression of DGKA was significantly higher in tumor tissues than in adjacent tissues in TCGA datasets. Besides, the comparison of the different clinicopathological features of NPC between high and low DGKA expression groups revealed that high DGKA expression was related to the survival status (p = 0.008). Statistical analysis indicates that high expression of DGKA is associated with poor prognosis in NPC. A monogram model was successfully established and demonstrated favorable predictive performance. Bioinformatics analysis showed that DGKA was associated with the activation of oncogenic signaling pathways and the reduction of anti-tumor CD8 + T cell infiltration. Conclusion High expression of DGKA is associated with poor overall survival of NPC patients. DGKA is expected to be a potential biomarker and therapeutic target for NPC.